2006
DOI: 10.1021/jp0631331
|View full text |Cite
|
Sign up to set email alerts
|

Single and Dual Cation Sites in Zeolites:  Theoretical Calculations and FTIR Spectroscopic Studies on CO Adsorption on K-FER

Abstract: Interaction of CO with K-FER zeolite was investigated by a combination of variable-temperature IR spectroscopy and computational study. Calculations were performed using omega(CO)/r(CO) correlation method in combination with a periodic density functional theory model. On the basis of agreement between experimental and calculated results, the following carbonyl complexes were identified: (i) mono- and dicarbonyl C-down complexes on single K(+) sites characterized by IR absorption bands at 2163 and 2161 cm(-1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
129
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(142 citation statements)
references
References 37 publications
11
129
2
Order By: Relevance
“…[15,41] However, the calculations on CO/zeolite Ca-A reported here show that there is only a negligible difference between the stability of CO adsorption complexes on single-and dual-cation sites provided comparison is made between complexes involving the same type of primary cation site (i.e., the cation interacting with the C atom of the CO molecule). A reason for this could be that, in the case of zeolite Ca-A, the bridged CO complexes formed on dual-cation sites deviate largely from a linear arrangement, as shown in Fig-A C H T U N G T R E N N U N G ure 3 g for the S2-S1 A complex.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…[15,41] However, the calculations on CO/zeolite Ca-A reported here show that there is only a negligible difference between the stability of CO adsorption complexes on single-and dual-cation sites provided comparison is made between complexes involving the same type of primary cation site (i.e., the cation interacting with the C atom of the CO molecule). A reason for this could be that, in the case of zeolite Ca-A, the bridged CO complexes formed on dual-cation sites deviate largely from a linear arrangement, as shown in Fig-A C H T U N G T R E N N U N G ure 3 g for the S2-S1 A complex.…”
mentioning
confidence: 78%
“…Di-and tri-carbonyls can also be formed in some cases when the CO equilibrium pressure is relatively high. [9,10,14] However, combined experimental and computational studies on CO adsorption on several alkali metal exchanged zeolites have recently shown that some gas adsorbing centres can actually involve two or more metal cations, [15,16] and such multiple-cation sites give rise to CO adsorption complexes that can differ from those formed on single-cation sites, not only in geometry, but also in CÀO stretching frequency and interaction energy (between CO and the cation site). While adsorption sites involving more than one cation are already well established for alkalimetal-exchanged zeolites, the case of zeolites containing divalent (extra-framework) cations is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some calculations with double UC were also performed. The CO 2 adsorption complexes on the most stable K + sites in the vicinity of each of four distinguishable framework Al positions (determined previously [42] ) were investigated. The following K + sites were considered ( Figure 1): I2/T2 and I2/T4 in the 8-R window on the intersection of perpendicular (P) and main (M) channels, M7/T3 in the M channel, and P8/T1 in the P cage (for details on site notation see ref.…”
mentioning
confidence: 99%
“…[45][46][47] In the case of CO adsorption on MFI, such a simultaneous adsorption of CO on dual cation sites was observed for samples with Si/Al = 14. [48] This threshold clearly depends on the size of the adsorbate and the zeolite topology.…”
Section: Discussionmentioning
confidence: 87%